Protein modification and maintenance systems as biomarkers of ageing. (November 2015) - Vanhooren, Valerie; Navarrete Santos, Alexander; Voutetakis, Konstantinos; Petropoulos, Isabelle; Libert, Claude; Simm, Andreas; Gonos, Efstathios S.; Friguet, Bertrand
Highlights: Background to research undertaken in the Mark-Age Project workpackage 3 is provided. Protein modifications and maintenance systems have been studied during ageing. Specific attention has been made on modifications of serum protein by carbohydrates. Maintenance was focused on clusterin, proteasome and methionine sulfoxide reductase. The fate of these modifications and maintenance systems during ageing is reviewed. Abstract: Changes in the abundance and post-translational modification of proteins and accumulation of some covalently modified proteins have been proposed to represent hallmarks of biological ageing. Within the frame of the Mark-Age project, the workpackage dedicated to "markers based on proteins and their modifications" has been firstly focused on enzymatic and non-enzymatic post-translational modifications of serum proteins by carbohydrates. The second focus of the workpackage has been directed towards protein maintenance systems that are involved either in protein quality control (ApoJ/Clusterin) or in the removal of oxidatively damaged proteins through degradation and repair (proteasome and methionine sulfoxide reductase systems). This review describes the most relevant features of these protein modifications and maintenance systems, their fate during ageing and/or their implication in ageing and longevity.